FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI PERTANIAN DI INDONESIA STUDI KASUS: KOMODITAS PADI - Apriinda, Khusnul Ainia; Mukin, Karolinda Kidi; Sayyidil Huda, Dhany Dharma (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
This study aims to analyze the effect of labor, People's Business Credit (KUR) financing, and farm road infrastructure on rice production in Indonesia. Using the Ordinary Least Squares (OLS) regression model on cross-section data from 34 provinces in 2023, this study found that farm road infrastructure has a positive and significant effect on rice production. Conversely, KUR financing shows a significant negative effect, indicating potential problems in the implementation and utilization of these funds. Labor and fertilizer use do not show a significant effect on rice production. The R-squared value of 26.58% indicates that there are other factors, such as technology or planting patterns, that affect rice production. This study recommends improving the quality of agricultural infrastructure, evaluating the distribution and use of KUR, and expanding the analysis in further research to include more diverse variables. The results of this study are expected to be the basis for formulating more effective policies in supporting the sustainability and productivity of the agricultural sector in Indonesia.